Modeling serviceability performance and ultimate capacity of corroded reinforced and prestressed concrete structures. (1st June 2021) - Marí, Antonio; Bairán, Jesús‐Miguel; Oller, Eva; Duarte, Noemi
Abstract: Corrosion reduces the area of reinforcement steel, affects its mechanical properties, the bond properties, and produces concrete cracking. Thus, reduction of the bearing capacity and stiffness, increments of deflections and redistribution of stresses and internal forces, in statically indeterminate structures, take place. In addition, the efficiency of strengthening systems of corroded structures depends on their state of stresses, strains and damage previously to strengthening. In this paper, a nonlinear and time dependent step by step analysis model for reinforced and prestressed concrete frames is presented. The model is capable of capturing the structural effects of corrosion and the effects of strengthening interventions, necessary to adequately assess corroded and strengthened structures. Several cases of corroded and strengthened structures are analyzed and the results discussed.